Effectiveness and treatment retention of TNF inhibitors when used as monotherapy versus comedication with csDMARDs in 15 332 patients with psoriatic arthritis. Data from the EuroSpA collaboration. Issue 11 (3rd June 2021) - Lindström, Ulf; Di Giuseppe, Daniela; Delcoigne, Bénédicte; Glintborg, Bente; Möller, Burkhard; Ciurea, Adrian; Pombo-Suarez, Manuel; Sanchez-Piedra, Carlos; Eklund, Kari; Relas, Heikki; Gudbjornsson, Bjorn; Love, Thorvardur Jon; et al.
Abstract : Background: Comedication with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) during treatment with tumour necrosis factor inhibitors (TNFi) is extensively used in psoriatic arthritis (PsA), although the additive benefit remains unclear. We aimed to compare treatment outcomes in patients with PsA treated with TNFi and csDMARD comedication versus TNFi monotherapy. Methods: Patients with PsA from 13 European countries who initiated a first TNFi in 2006–2017 were included. Country-specific comparisons of 1 year TNFi retention were performed by csDMARD comedication status, together with HRs for TNFi discontinuation (comedication vs monotherapy), adjusted for age, sex, calendar year, disease duration and Disease Activity Score with 28 joints (DAS28). Adjusted ORs of clinical remission (based on DAS28) at 12 months were calculated. Between-country heterogeneity was assessed using random-effect meta-analyses, combined results were presented when heterogeneity was not significant. Secondary analyses stratified according to TNFi subtype (adalimumab/infliximab/etanercept) and restricted to methotrexate as comedication were performed. Results: In total, 15 332 patients were included (62% comedication, 38% monotherapy). TNFi retention varied across countries, with significant heterogeneity precluding a combined estimate. Comedication was associated with better remission rates, pooled OR 1.25 (1.12–1.41). Methotrexate comedication was associated with improved remission for adalimumab (OR 1.45 (1.23–1.72)) and infliximab (OR 1.55 (1.21–1.98)) and improved retention for infliximab. No effect of comedication was demonstrated for etanercept. Conclusion: This large observational study suggests that, as used in clinical practice, csDMARD and TNFi comedication are associated with improved remission rates, and specifically, comedication with methotrexate increases remission rates for both adalimumab and infliximab.